Study of buccal epithelium as a method of diagnosis of uterine myoma - Savytskyi, I.V.; Magdenko, A.K.; Mjastkovskaja, I.V.; Grigor’ev, P.E. (Актуальні проблеми транспортної медицини, 2017)
Uterine myoma is one of the reasons that lead to infertility and a number of serious complications during pregnancy. Relevant is to find methods for early diagnosis of this disease. At the same time research buccal epithelium has several advantages because of its painless and informative, and is characterized by ease of collection of material for research. Below you will see the results of the study nuclei of buccal epithelium in patients with uterine cancer compared with the control group. For a group of patients diagnosed with uterine fibroids detected buccal epithelium following characteristics: shape core spindle and uncertain; membrane nucleus split evenly thick, sealed, reinforced sides and loosened; color core dark, dark to a mirror, with grain sizes. Миома матки является одной из причин, приводящих к бесплодию и ряду серьезных осложнений во время беременности. Необходимо найти
методы ранней диагностики этого заболевания. В то же время исследование буккального эпителия имеет ряд преимуществ из-за его безболезненности, информативности и простоты сбора материала для исследования. В статье приведены результаты изучения ядер буккального эпителия у пациентов с раком матки по сравнению с контрольной группой. У пациентов с миомой матки были выявлены морфо-структурные изменения ядер клеток буккального эпителия по сравнению с контрольной группой. Міома матки є однією з причин, що призводять до безпліддя і ряду серйозних ускладнень під час вагітності.
Необхідно знайти методи ранньої діагностики цього захворювання. У той же час дослідження буккального епітелію має ряд переваг через його безболісність, інформативність та простоту збору матеріалу для дослідження. У статті наведені результати вивчення ядер букального епітелію у пацієнтів з раком матки в порівнянні з контрольною групою. У пацієнтів з міомою матки були виявлені морфоструктурні зміни ядер клітин букального епітелію в порівнянні з контрольною групою.